2020
DOI: 10.1051/0004-6361/201937000
|View full text |Cite
|
Sign up to set email alerts
|

ISPY-NACO Imaging Survey for Planets around Young stars

Abstract: Context. The occurrence rate of long-period (a 50 au) giant planets around young stars is highly uncertain since it is not only governed by the protoplanetary disc structure and planet formation process, but also reflects both dynamical re-structuring processes after planet formation as well as possible capture of planets not formed in situ. Direct imaging is currently the only feasible method to detect such wide-orbit planets and constrain their occurrence rate. Aims. We aim to detect and characterise wide-or… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
58
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 42 publications
(63 citation statements)
references
References 230 publications
4
58
0
Order By: Relevance
“…Surveys carried out by space-based observatories such as Spitzer, Herschel, and WISE have uncovered hundreds of stars within ∼200 pc with a significant infrared excess in their spectral energy distributions at 22-24μm suggesting the presence of warm circumstellar dust (e.g., Trilling et al 2008;Carpenter et al 2009;Cotten & Song 2016;Patel et al 2017;Silverberg et al 2018), or a colder component identified by an excess at 70-160 μm (e.g., Hillenbrand et al 2008;Matthews et al 2010;Eiroa et al 2013;Sibthorpe et al 2018). The identification of these circumstellar disks has also coincided with several high-contrast imaging surveys targeting stars with an infrared excess (e.g., Janson et al 2013;Rameau et al 2013;Nielsen et al 2019;Launhardt et al 2020). Scattered-light images of debris disk systems in the optical or near-infrared (2 μm) returned by these surveys (e.g., Esposito et al 2020) are particularly powerful for characterizing planetary systems, as the morphology of stable debris belts may reveal the gravitational influence of giant planets sculpting the dust distribution through resonant interactions (e.g., Wyatt 2003;Chiang et al 2009;Morales et al 2011;Su et al 2013;Matthews et al 2018).…”
Section: Introductionmentioning
confidence: 53%
“…Surveys carried out by space-based observatories such as Spitzer, Herschel, and WISE have uncovered hundreds of stars within ∼200 pc with a significant infrared excess in their spectral energy distributions at 22-24μm suggesting the presence of warm circumstellar dust (e.g., Trilling et al 2008;Carpenter et al 2009;Cotten & Song 2016;Patel et al 2017;Silverberg et al 2018), or a colder component identified by an excess at 70-160 μm (e.g., Hillenbrand et al 2008;Matthews et al 2010;Eiroa et al 2013;Sibthorpe et al 2018). The identification of these circumstellar disks has also coincided with several high-contrast imaging surveys targeting stars with an infrared excess (e.g., Janson et al 2013;Rameau et al 2013;Nielsen et al 2019;Launhardt et al 2020). Scattered-light images of debris disk systems in the optical or near-infrared (2 μm) returned by these surveys (e.g., Esposito et al 2020) are particularly powerful for characterizing planetary systems, as the morphology of stable debris belts may reveal the gravitational influence of giant planets sculpting the dust distribution through resonant interactions (e.g., Wyatt 2003;Chiang et al 2009;Morales et al 2011;Su et al 2013;Matthews et al 2018).…”
Section: Introductionmentioning
confidence: 53%
“…Some exoKuiper belt host systems even have companions in the brown dwarf or low stellar mass regime, suggesting that their likely formation through gravitational instability (Boss 1997(Boss , 2003(Boss , 2011Vorobyov 2013) is compatible with the formation of massive Kuiper belt analogues, e.g. HR 2562 (Konopacky et al 2016), HD 193571 (Musso Barcucci et al 2019) HD 92536 (Launhardt et al 2020), andHD 206893 (Milli et al 2017). The latter is the subject of this paper.…”
Section: Introductionmentioning
confidence: 99%
“…We combined the different sources of uncertainty in quadrature for each parameter. For NACO, Launhardt et al (2020) reported plate scale and true north measurements of 27.2 ± 0.1 mas/px and 0.57 ± 0.12 • based on all their astrometric measurements between December 2015 and March 2018, respectively. We adopted these values, but conservatively adopted an uncertainty of 0.5 • for the PA of TN, to account for any difference between for the different epochs of observations.…”
Section: Astrometrymentioning
confidence: 99%